LUPA: a workflow engine - Arráiz, Emely (2006)
Workflow Management Systems depend on a Workflow Enactment Service having several interfaces to establish communication with external applications, manage persistent information and exchange it with similarly capable systems. The study of business processes has shown multiple workflow patterns that have been modelled and implemented in several engines. The Workflow Management Council has combined commercial and academic efforts towards a standard structure for engines and information exchange regarding workflow processes. LUPA is aWorkflow Engine designed around theWorkflow Management Council Reference Model that implements basic workflow patterns with a graphical syntax, establishing their semantics on Interpreted Petri Nets with extensions. It provides a new Cancellation workflow pattern, that has also been used to provide an Iteration pattern with guaranteed termination.